A chance encounter: Levison's inspiration. (2nd February 2020) - Sinclair, Michelle
Abstract : In the course of her work with dependant older patients, senior dental nurse and oral health educator and tutor, Michelle Sinclair, stumbled upon a person she has revered all her working life…